2015
DOI: 10.1016/j.indcrop.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-ESI-MSn characterization of phenolic compounds, terpenoid saponins, and other minor compounds in Bituminaria bituminosa

Abstract: Tandem mass spectrometry a b s t r a c t Bituminaria bituminosa is a wild legume that can endure drastic conditions, including contaminated and degraded soils. It has been traditionally used as feeding for livestock, and different uses in folk medicine are known. The chemical composition of leaves and flowers from B. bituminosa is presented for the first time. The screening of phytochemical compounds was carried out using high-performance liquid chromatography with electrospray ionization mass spectrometric de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…These compounds showed a similar MS/MS fragmentation pattern with major fragments at m/z 229, 211 and 183 in MS 2 , MS 3 and MS 4 , respectively. They were tentatively identified in comparison to literature data as oxylipins, fatty acid oxidation products: oxo‐dihydroxy‐octadecenoic acid and trihydroxy‐octadecenoic acid …”
Section: Resultsmentioning
confidence: 99%
“…These compounds showed a similar MS/MS fragmentation pattern with major fragments at m/z 229, 211 and 183 in MS 2 , MS 3 and MS 4 , respectively. They were tentatively identified in comparison to literature data as oxylipins, fatty acid oxidation products: oxo‐dihydroxy‐octadecenoic acid and trihydroxy‐octadecenoic acid …”
Section: Resultsmentioning
confidence: 99%
“…Nine apigenin derivatives were tentatively characterized, most of them C-glycosides. Compound 12 was identified as vicenin-2 (apigenin-6,8-di-C-hexoside) considering bibliographic data (Llorent-Martínez et al, 2015 ). With a similar fragmentation pattern, compound 26 was also characterized as an apigenin-di-C-hexoside.…”
Section: Resultsmentioning
confidence: 99%
“…Another compound that deserves prominence, identified as rosmarinic acid (m/z 359) that was found in samples A, D and F, presents anti-inflammatory action and has anti-pathogenic properties against bacterial and viral agents and neuroprotective effects. 37,38,43 According to El-Zaeddi et al 45 rosmarinic acid has already been reported in aromatic herbs. The samples A and B have the presence of parsley (Petroselinum crispum) an aromatic herb as a common ingredient among the samples.…”
Section: Chemical Profile Of Mixed Beverages By Ps-msmentioning
confidence: 99%